2019
DOI: 10.1371/journal.pone.0217066
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling revealed diverse gene expression patterns in poplar (Populus × euramericana) under different planting densities

Abstract: Certain plant genotypes can achieve optimal growth under appropriate environmental conditions. Under high planting density conditions, plants undergo competition for uptake and utilization of light and nutrients. However, the relationship between whole-genome expression patterns and the planting density in perennial woody plants remains unknown. In this study, whole-genome RNA sequencing of poplar ( Populus × euramericana ) was carried out at three different sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 70 publications
(69 reference statements)
2
17
0
Order By: Relevance
“…The plant hormone abscisic acid (ABA) is a developmental signal that responds to environmental stimuli.2C type protein phosphatases (PP2Cs) is closely related to abscisic acid (ABA) signaling pathway and play a role through the negative regulation of ABA response [51,52]. SUAR, IAA and PP2C involved in plant hormone signal transduction pathway were higher in HD than LD, which was consistent with the findings in poplar [16]. In addition, the Aux / IAA related genes were down regulated under HD when compared to LD.…”
Section: Plos Onesupporting
confidence: 80%
See 1 more Smart Citation
“…The plant hormone abscisic acid (ABA) is a developmental signal that responds to environmental stimuli.2C type protein phosphatases (PP2Cs) is closely related to abscisic acid (ABA) signaling pathway and play a role through the negative regulation of ABA response [51,52]. SUAR, IAA and PP2C involved in plant hormone signal transduction pathway were higher in HD than LD, which was consistent with the findings in poplar [16]. In addition, the Aux / IAA related genes were down regulated under HD when compared to LD.…”
Section: Plos Onesupporting
confidence: 80%
“…The comparative transcriptome analysis of cassava leaves under full day and natural shade conditions found that the gene expression profiles in both cases showed similar developmental changes, the expression of hormone related transcription factors and genes were influenced by shade [15]. The transcriptome analysis of poplar and maize with different densities revealed the differential expression of genes related to plant hormones, photosynthetic complexes and photosynthetic antenna proteins [16,17]. However, there are few studies on the effect of planting density on gene expression, which need more research.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the functions of POD genes in the growth and development of Betula Platyphylla × Betula Pendula, their expression pro les in different tissues (including root, xylem, young leaf and ower) were analyzed with publicly available transcriptome data. Of the 90 BpPODs, 69 genes were expressed in one or more birch tissues, while 21 BpPOD genes exhibited no expression in various individual tissues (Relative expression value > 0 as basal expression) [40]. The heat map (Figure 7) demonstrated that most BpPODs had tissue-speci c or preferential expression patterns.…”
Section: Tissue-speci C Expression Of Bppodsmentioning
confidence: 99%
“…Many previous studies have shown that intraspecific interactions can affect the morphological characteristics of the plant canopy (Song et al, 2016) and roots (Khan et al, 2018) as well as the plant metabolic level (Kuai et al, 2016), ultimately influencing plant growth and quality (Huang et al, 2019). The effects of intraspecific interactions on plant performance can be easily realized by altering the planting density (Broekman et al, 2019;Ning et al, 2019). A suitable density ensures the normal growth of individual plants and entire population through coordinate utilization of water, light, temperature, and nutrients (Ning et al, 2019).…”
Section: Introductionmentioning
confidence: 99%